Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan 3M (Menggunting, Melipat, Menempel) Pada Peserta Didik Kelas 3 Di SDN 08 Mataram Tahun Ajaran 2022/2023 - Sudarmini, Luh Ayu; Parameswari, Kinanti Idha; Fatmawati, Elisa; Darmiany, Darmiany (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
Elementary school education has a very important role for the growth and development of students at the age of 7-12 years. Motoric development in students in elementary schools needs special attention and training to develop it to the fullest. Motor skills develop along with the maturity of nerves and muscles. Therefore every movement produced by students is the result of interaction patterns of various systems in the body that are controlled by the brain. This classroom action research aims to improve fine motor skills through activities (cutting, folding, pasting) in grade III students at SDN 08 Mataram. Data collection techniques are carried out through observation and data collection. Data analysis uses percentage description. The results of this classroom action research showed that there was an increase in the fine motor development of class III students through activities (cutting, folding, pasting). This can be seen from the average proportion of the results of the fine motor skills of class III students before the action was 33%, cycle 1 was 49%, and cycle 2 was 63%. The increase in students' fine motor skills is due to factors from the teacher who provides stimulus or treatment to students to make a product by involving the flexibility of the fingers through activities. From this study it can be concluded that class III students at SDN 08 Mataram have experienced an increase in motor development.